Speech-language pathology and audiology: transformation in teaching, research and service delivery - Isabel C Uys; Rene Hugo (AOSIS, 1997)
Tins article aims at a presentation of transformation in communication pathology. Opsomming Die doel van hierdie artikel is om transformasie in kommunikasiepatologie voor te hou. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.